2018
DOI: 10.1128/iai.00069-18
|View full text |Cite
|
Sign up to set email alerts
|

ATGGenes Influence the Virulence of Cryptococcus neoformans through Contributions beyond Core Autophagy Functions

Abstract: The process of autophagy is conserved among all eukaryotes from yeast to humans and is mainly responsible for bulk degradation of cellular contents and nutrient recycling during starvation. Autophagy has been suggested to play a role in the pathogenesis of the opportunistic human fungal pathogen , potentially through a contribution to the export of virulence factors. In this study, we showed that deletion of each of the, ,, and genes in leads to autophagy-related phenotypes, including impaired amino acid homeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 83 publications
3
11
1
Order By: Relevance
“…The atg7 mutant cause slight growth defect at both 30 • C and 37 • C and produce less melanin than the WT strain after 48-h incubation. These atg mutants are able to produce a polysaccharide capsule similar in size to WT (Ding et al, 2018). However, there are some differences between our study and that of Ding et al The atg7 and atg8 mutants resulted in slight sensitivity to high temperatures, and these four atg mutants led to smaller capsules (Figure 4 and Supplementary Figure S4).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…The atg7 mutant cause slight growth defect at both 30 • C and 37 • C and produce less melanin than the WT strain after 48-h incubation. These atg mutants are able to produce a polysaccharide capsule similar in size to WT (Ding et al, 2018). However, there are some differences between our study and that of Ding et al The atg7 and atg8 mutants resulted in slight sensitivity to high temperatures, and these four atg mutants led to smaller capsules (Figure 4 and Supplementary Figure S4).…”
Section: Discussioncontrasting
confidence: 61%
“…WT-sized bands were amplified in the correct transformants, but a larger band was amplified in the defective strains ( Supplementary Figure S4A). Then, we measured the high temperature tolerance of these strains as well as capsule induction in low-iron medium and melanin production on L-DOPA agar plates (Ding et al, 2018). The atg7 and atg8 strains showed slight sensitivity to high temperatures; however, normal phenotype was restored in the respective complementation strains (Supplementary Figure S4B).…”
Section: Contribution Of Atg Genes To Traditional Virulent Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by a study from Nikola et al, [ 48 ] that shows differences in the recruitment pattern of LC3 the between antibody-mediated and opsonin-mediated autophagy of C. neoformans . Besides the possibility that C. neoformans is dependent on a functioning autophagic machinery, there is evidence that it is dependent on various Atgs beyond their core function in autophagy [ 60 ].…”
Section: Autophagy In Antifungal Immunity—friend or Foementioning
confidence: 99%
“…Also, the ATG7 gene has been shown to play roles in the virulence of C. neoformans (Oliveira et al, 2016). Recently, four ATG genes, ATG1, ATG7, ATG8, and ATG9, including the two (ATG7 and ATG8) studied before, were functionally examined in C. neoformans and the results suggested that ATG1, ATG7, ATG8, and ATG9 each make different contributions to C. neoformans virulence, indicating Cryptococcus virulence may not be utterly dependent on core autophagy functions (Ding et al, 2018). More recently, Zhao et al constructed 22 autophagy-deficient strains in C. neoformans and found that 12 of them showed remarkable virulence attenuation in the invertebrate (Galleria mellonella) model of cryptococcosis (Zhao et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%